Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

f(x) = x² - 4
explanation of inverse for this function


Sagot :

Answer:

[tex]f^{-1}(x)[/tex] = ±√(x + 4)

Step-by-step explanation:

f(x) = x² - 4

substitute y for f(x):   y = x² - 4

Swap y and x:           x = y² - 4

Make y the subject:  x + 4 = y²  ⇒  y = ±√(x + 4)

substitute [tex]f^{-1}(x)[/tex] for y:  [tex]f^{-1}(x)[/tex] = ±√(x + 4)